Fertilization defects in sperm from Cysteine-rich secretory protein 2 (Crisp2) knockout mice: Implications for fertility disorders - Brukman, Nicolás Gastón (2016)
STUDY HYPOTHESIS We hypothesize that fertility disorders in patients with aberrant expression of Cysteine-RIch Secretory Protein 2 (CRISP2) could be linked to the proposed functional role of this protein in fertilization. STUDY FINDING Our in vivo and in vitro observations reveal that Crisp2-knockout mice exhibit significant defects in fertility-associated parameters under demanding conditions, as well as deficiencies in sperm fertilizing ability, hyperactivation development and intracellular Ca2+ regulation. WHAT IS KNOWN ALREADY Testicular CRISP2 is present in mature sperm and has been proposed to participate in gamete fusion in both humans and rodents. Interestingly, evidence in humans shows that aberrant expression of CRISP2 is associated with male infertility. STUDY DESIGN, SAMPLES/MATERIALS, METHODS A mouse line carrying a deletion in the sixth exon of the Crisp2 gene was generated. The analyses of the reproductive phenotype of Crisp2−/− adult males included the evaluation of their fertility before and after being subjected to unilateral vasectomy, in vivo fertilization rates obtained after mating with either estrus or superovulated females, in vitro sperm fertilizing ability and different sperm functional parameters associated with capacitation such as tyrosine phosphorylation (by western blot), acrosome reaction (by Coomassie Blue staining), hyperactivation (by computer-assisted sperm analysis) and intracellular Ca2+ levels (by flow cytometry). MAIN RESULTS AND THE ROLE OF CHANCE Crisp2−/− males presented normal fertility and in vivo fertilization rates when mated with estrus females. However, the mutant mice showed clear defects in those reproductive parameters compared with controls under more demanding conditions, i.e. when subjected to unilateral vasectomy to reduce the number of ejaculated sperm (n = 5; P< 0.05), or when mated with hormone-treated females containing a high number of eggs in the ampulla (n ≥ 5; P< 0.01). In vitro fertilization studies revealed that Crisp2−/− sperm exhibited deficiencies to penetrate the egg vestments (i.e. cumulus oophorus and zona pellucida) and to fuse with the egg (n ≥ 6; P< 0.01). Consistent with this, Crisp2-null sperm showed lower levels of hyperactivation (n = 7; P< 0.05), a vigorous motility required for penetration of the egg coats, as well as a dysregulation in intracellular Ca2+ levels associated with capacitation (n = 5; P< 0.001). LIMITATIONS, REASONS FOR CAUTION The analysis of the possible mechanisms involved in fertility disorders in men with abnormal expression of CRISP2 was carried out in Crisp2 knockout mice due to the ethical and technical problems inherent to the use of human gametes for fertilization studies. WIDER IMPLICATIONS OF THE FINDINGS Our findings in mice showing that Crisp2−/− males exhibit fertility and fertilization defects under demanding conditions support fertilization defects in sperm as a mechanism underlying infertility in men with aberrant expression of CRISP2. Moreover, our observations in mice resemble the situation in humans where fertility disorders can or cannot be detected depending on the accumulation of own individual defects or the fertility status of the partner. Finally, the fact that reproductive defects in mice are masked by conventional mating highlights the need of using different experimental approaches to analyze male fertility. STUDY FUNDING AND COMPETING INTEREST(S) This study was supported by the World Health Organization (H9/TSA/037), the National Research Council of Argentina (PIP 2009-290), the National Agency for Scientific and Technological Promotion of Argentina (PICT 2011, 2023) and the Rene Baron Foundation to P.S.C. and by the MEXT of Japan to M.I. The authors declare that there are no conflicts of interest.